Leadership capacity and financial reporting quality in local government authorities: evidence from Tanzania - Charles Kunyonga Matekele; Cosmas Simon Mbogela; Chirongo Moses Keregero (African Business Management Journal, 2025)
This study examines the connection between dimensions of leadership capacity and financial reporting quality in Tanzanian local government authorities. Primary data were collected from 126 local government authorities, involving 225 final accounts-accountants and internal auditors, using a survey instrument. The hypotheses were tested using partial least squares structural equation modelling. Results indicate that financial reporting quality in local government authorities is positively and significantly explained by accountability, rule-following, network governance, and political loyalty leadership. This study provides implications for restructuring policies and regulations related to the composition of the full council and its committees, by introducing professionalism, in order to separate political and financial reporting practices in local government authorities. Consequently, the quality of public sector financial reporting will be improved, and conducive environments for the delivery of social services among local government authorities will be assured due to the embrace of accountability, rule-following, and network governance leadership among local government authorities.